ANALISIS KETERLIBATAN HIDUP MENGGEREJA SISWA KATOLIK SEKOLAH DASAR KOTA BENGKULU DI PAROKI SANTO YOHANES PENGINJIL BENGKULU - Sinaga, Juliana Sriana (STP St. Bonaventura Medan, 2022)
Elementary School Catholic students are Christian believers who are experiencing a process of growth and development both physically and spiritually. The very rapid development of technology and information has had a positive influence in all areas of life. However, it also has a negative impact on children's growth and development. This has encouraged many parties, especially parents, to move quickly and be more serious in responding to this matter, in relation to mentoring their children's faith. This research on the involvement of Catholic elementary school students in Bengkulu City is expected to be able to measure the involvement of students in church life. By using quantitative research methodology, it was found that there are still many Catholic elementary school students who are not or are not involved in church life. This becomes a focal point for parents to increase their attention to their children